Ownership of Health Insurance and Use of Traditional Medicine - Adelia Arsela; Dinda Rama Fadillah; Suci Wulandari; Tiara Arianti Tri Utami (Pena Cendekia Insani, 2021)
Since the inception of social health insurance, patient demand for traditional medicine services in health care facilities has decreased. There are over a dozen statutes, regulations, and policies governing the use of traditional medicines in health care settings. The service, implementation of OT guarantees with social health insurance, clinician readiness, and government support are all examined. This study aims to ascertain who owns social health insurance and who utilizes traditional health services. This is a quantitative study with a cross-sectional design conducted in North Sumatra Province in July-August 2021. The sample for this study consisted of respondents from North Sumatra Province, with 1000 respondents via Google Form. This study analyzed data using univariate analysis. The findings indicate that 59.6 per cent of respondents experienced illness in the last 30 days of the study, with symptoms ranging from mild to severe. 338 (33.8 per cent) of respondents had never used traditional medicine. The majority of people in urban areas prefer modern health facilities to traditional medicine total of 194 respondents (19.4 per cent) prefer to practice traditional medicine independently. Traditional medicine services are incorporated into the path of prevention, promotion, and mild curative efforts, both as adjuvants and complements to conventional medicine. Traditional medicine can be financed through government funding but has not been done so. A ministerial decree requiring health facilities to provide services using traditional medicines is still required.